The Feasibility of Ready-to-Wear Clothing with Bamboo Tree Ideas Source Using Weaving Techniques - Widyaasih, Dyah Ayu Nimas; Prasetyaningtyas, Wulansari (Journal of Creativity Student, 2026)
This study aims to evaluate the feasibility of ready-to-wear clothing with bamboo tree ideas through the application of woven techniques as the main element of design. The study used a descriptive quantitative method with assessment by expert panelists and trained panelists. The research instrument included six assessment indicators, namely design, size, sewing technique, aesthetics, fashion performance, and specialty. The validity of the instrument was tested using the Aiken's V index and the reliability using the Intraclass Correlation Coefficient (ICC). Data analysis was carried out through the calculation of the percentage of the eligibility level. The results of the study showed that fashion obtained an average eligibility percentage of 89.71% with the very feasible category. The assessment of expert panelists was 89.33% and trained panelists were 90.09%, both of which were in the very feasible category. These results show that the application of weaving techniques in ready-to-wear clothing is able to provide unique aesthetic value while fulfilling the aspects of construction, comfort, and the function of fashion as a ready-to-wear product.